Dinamika Kaum LGBT, Pendidikan Keislaman, dan Sikap Kemanusiaan: Studi Fenomenologi di Perguruan Tinggi di Malang - Muhammad Qorib; Umiarso Umiarso (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2019)
This research aims to comprehend and discover the construction of actiontowards LGBT students at a university in Malang. Next, this research focuses upon the accommodative-persuasive attitude, which is influenced by humanism, of the academic community towards LGBT students. For that reason, this study employs phenomenological approach to acquire substantive meaning within the dynamics of LGBT students. This study suggests that LGBT is formed not only form naturally (essentialism), but also through social environment (social constructionism). Apart from the two major views upon how LGBT is developed, the academic communities do not legitimize any treatments against LGBT students under rationale that LGBT community is less than God’s creation. The academic communities have been attempting to “realign” the LGBT students to their nature. They believe that LGBT students have the fundamental rights as God’s creation (as in line with other human being) and those rights must get attention from all elements of academic communities.